Identifikasi Ketidaksesuaian Pengobatan pada Proses Rekonsiliasi Obat di Instalasi Rawat Inap Rumah Sakit - Manuel, Jennike T.; Wiyono, Wenny I.; Jayanti, Meilani (Jurnal Biomedik : JBM, 2021)
Abstract: Reconciliation is one of the proces that prevents drug-related problems, medication errors, and drug-related adverse events. This study aimed to identify treatment mismatches based on the results of drug reconciliation in 49 patients from the January to March 2020 study period. This research has been descriptive study with prospective data collection in inpatient installation CVBC (Cardiovascular and Brain Center) and Irina F Jantung, Prof. Dr. R. D. Kandou Manado.The results of the study based on patient characteristics showed that the number of male patients was greater than that of women, namely 31 patients and the highest number of patients was in the age group (60 - 69) as many as 23 patients. The results showed that the majority of patients were male as many as 31 patients and the most in the age group (60-69) as many as 23 patients. The characteristics of the number of drugs shown in the drug history data (BPMH), the majority of patients consumed <5 types of drugs, were 25 patients, in the ER Most consumed <5 types of drugs as many as 27 patients and also the majority of patients received ≥5 types of drugs while in the inpatient installation of 27 patients and when they left the hospital the majority of patients were given ≥5 types of drugs, namely 34 patients. The most widely used drugs are cardiovascular system drugs with a percentage of BPMH (95.92%), IGD (100%), in inpatient installations (100%) and out of prescription (100%) and the second is digestive system drugs. The percentage of unintentional discepancies was incomplete prescription (10.2%), omission medication (10.2%), and intentional discrepancies (100%).Keywords: medication discrepancies, medication reconciliation  Abstrak: Rekonsiliasi merupakan salah satu proses yang dilakukan untuk mencegah terjadinya kesalahan obat. Penelitian ini bertujuan mengidentifikasi ketidaksesuaian pengobatan berdasarkan hasil rekonsiliasi obat pada 49 pasien periode Januari–Maret 2020. Desain penelitian deskriptif dengan pengambilan data secara prospektif di instalasi rawat inap CVBC (Cardiovascular and Brain Center) dan Irina F Jantung RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian menunjukkan mayoritas pasien adalah laki-laki sebanyak 31 pasien dan terbanyak pada kelompok usia (60-69) sebanyak 23 pasien. Karakteristik jumlah obat ditunjukkan pada data riwayat obat (BPMH) mayoritas pasien mengkonsumsi <5 jenis obat sebanyak 25 pasien, di IGD Sebagian besar mengkonsumsi <5 jenis obat sebanyak 27 pasien dan juga mayoritas pasien menerima  jenis obat saat di Instalasi rawat inap sebesar 27 pasien dan saat keluar rumah sakit mayoritas pasien diberikan  jenis obat yaitu 34 pasien. Obat yang paling banyak digunakan yaitu obat sistem kardiovaskular dengan presentase pada BPMH (95,92%), IGD (100%), di Instalasi rawat inap (100%) dan pada resep keluar (100%) dan yang kedua obat sistem pencernaan. Persentase ketidaksesuaian pengobatan yaitu Incomplete prescription sebesar (10,2%), Omission medication (10,2 %), dan ketidaksesuaian yang disengaja (100%).Kata kunci: rekonsiliasi, ketidaksesuaian pengobatan